Identification and Temporal Expression Analysis of Conserved and Novel MicroRNAs in the Leaves of Winter Wheat Grown in the Field - Li, Yong-Fang; Wei, Kangning; Wang, Menglei; Wang, Li; Cui, Junxia; Zhang, Daijing; Guo, Junqiang; Zhao, Miao; Zheng, Yun (Frontiers in Genetics, 2019)
Background: Vernalization is an essential process for winter wheat to switch from vegetative growth to reproductive growth. This character determines potential wheat planting area, grain yield and quality. MicroRNA (miRNA) is a class of regulatory small RNA (sRNA) which plays critical roles in plant growth and development. However, less information is known about the regulation mechanism of miRNA during winter wheat vernalization. In this study, four sRNA libraries from wheat leaves at different development stages were analyzed to identify known and novel miRNAs and understand their functions in wheat development. Results: We examined miRNA expression in winter wheat leaves in three vegetative stages and one reproductive stage using high throughput sequencing method. Totally, we identified 373 known miRNAs, 55 novel miRNAs and 27 putative novel miRNAs. Many miRNAs were significantly induced or repressed when wheat transit from vegetative growth to reproductive growth. Among them, miR156 and miR172 showed the same pattern as in other plant. miR408, miR167, miR528, miR9672 and 17 novel miRNA function as flowering promoter, while, miR165, miR5200, miR9778, miR9662 and 33 novel miRNAs function as flowering repressor. We also identified a set of miRNAs that were predominantly expressed in only one or two stages. We verified the expression patterns of a number of representative miRNAs using RT-qPCR analysis, the result is consistent with that of the deep-sequencing method. Potential target genes for these miRNAs were predicted; moreover, 6 novel target genes for 4 wheat species specific miRNAs and 2 novel miRNAs were verified using RLM-5RACE assay. Conclusions: Besides of known miRNAs, 82 novel miRNAs were identified in this study. A subset of miRNAs was found responsive to wheat vernalization. These results indicate that miRNA is a kind of key non-coding regulation factor that is involved in many biological processes during wheat growth and development. Our study provides valuable information for deep understanding the regulatory mechanism of miRNAs in winter wheat vernalization.